Carmencristina Moreno at Bernie and Marian Meyerson's Home - Watkins, Howard::::::::: (1979)
Marian Meyerson, Bernie Meyerson, Carmencristina Moreno playing acoustic guitar Sitting on backyard wooden deck benches; black guitar case